2001
DOI: 10.1001/archopht.119.11.1629
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Gene Expression in Human Donor Corneas

Abstract: To use microarray analysis to identify genes expressed in human donor corneas and to create a preliminary, comprehensive database of human corneal gene expression. Methods: A complementary DNA (cDNA) library was constructed from transplant-quality, human donor corneas. Biotin-labeled RNA was transcribed from the cDNA library and hybridized in duplicate to microarrays containing approximately 5600 human genes. Results were analyzed using a gene database of the National Institutes of Health, Bethesda, Md. Revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…2,3 A previous work described the use of complementary DNA (cDNA) microarray technology to provide a gene expression profile of the human cornea, characterizing some 1200 genes. 4 Microarrays, however, are limited by the finite number of oligonucleotide sequences localized on a chip and are not able to identify the expression of novel genes.…”
mentioning
confidence: 99%
“…2,3 A previous work described the use of complementary DNA (cDNA) microarray technology to provide a gene expression profile of the human cornea, characterizing some 1200 genes. 4 Microarrays, however, are limited by the finite number of oligonucleotide sequences localized on a chip and are not able to identify the expression of novel genes.…”
mentioning
confidence: 99%
“…Corneas were fixed for 30 min in phosphate-buffered saline (PBS) containing 1% glutaraldehyde, then rinsed thrice in cold PBS containing 2 m M of MgCl 2 . Corneas were then incubated for 30 min at 37 ° C in a solution containing 0.2% X-Gal (5-bromo-4-chloro-3-inodyl-␤ -galactosidase, Sigma), 10 6 , which gave a blue coloration to the transfected ECs. After rinsing in distilled water, corneas were placed on a backlit table and photographed at low magnification.…”
Section: Transfection With ␤ -Galactosidase: Measurement Of Transfectmentioning
confidence: 99%
“…Overexpression of certain genes of interest and the inactivation of others may allow determination of the role and interactions of certain proteins in the corneal endothelium. This is all the more important as insight into the genes expressed most specifically in the ECs of healthy subjects and in patients with Fuchs' dystrophy was provided several years ago [6][7][8][9][10] . In the long term, the prospect of local gene therapy for management of early stages of Fuchs' dystrophy and for modulation of accelerated EC loss during corneal preservation and post-graft rejection is equally attractive.…”
mentioning
confidence: 99%
“…In an effort to create a preliminary database of human corneal gene expression Jun et al (2001) performed a microarray study using a cDNA array constructed from human donor corneas. The study showed a wide range of genes being expressed including, genes for six types of collagen subunit were found to be expressed (e.g.…”
Section: Introductionmentioning
confidence: 99%